2017
DOI: 10.1111/echo.13576
|View full text |Cite
|
Sign up to set email alerts
|

Single right coronary artery with absence of the left main coronary artery, left anterior descending artery, and circumflex artery

Abstract: Single coronary artery is an extremely rare congenital coronary anomaly in which the entire coronary arterial system arises from a solitary ostium. The Lipton's classification is used for single coronary artery anomalies. Herein, we present a 72-year-old woman with single coronary artery anomaly admitted with atypical chest pain. Coronary angiography and multidetector computed tomography coronary angiography findings were shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Eighty-eight studies were excluded due to discrepancies between their primary and secondary results compared to those of this review, or because they failed to meet the established criteria for good data extraction. Therefore, 39 articles [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were selected for this study ( n = 140,137) (including patients, images, and cadavers) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighty-eight studies were excluded due to discrepancies between their primary and secondary results compared to those of this review, or because they failed to meet the established criteria for good data extraction. Therefore, 39 articles [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] were selected for this study ( n = 140,137) (including patients, images, and cadavers) ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 39 studies included in this review (as listed in Table 1 and Table 2 ), 19 articles are from Asia [ 11 , 12 , 13 , 19 , 20 , 21 , 23 , 27 , 33 , 35 , 36 , 37 , 39 , 41 , 43 , 45 , 46 , 47 , 48 ], 10 are from Europe [ 13 , 16 , 17 , 22 , 26 , 30 , 31 , 32 , 34 , 40 ], 8 are from North America [ 10 , 15 , 18 , 24 , 25 , 29 , 38 , 44 ], 1 is from South America [ 28 ], and 1 is from Oceania [ 42 ]. Therefore, the total number of subjects is 140,137, among whom 811 presented coronary artery variants, with an average age of diagnosis of 41.4 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A case of congenital absence of left circumflex artery with the presence of a super dominant right coronary artery has also been reported [6]. Saglam et al (2017) [7] have presented a case of single right coronary artery with the absence of left coronary, anterior interventricular, and circumflex arteries. Iliev et al (2018) [8] have reported the common trunk origin of left coronary artery with a super dominant right coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…According to our literature review, a single RCA is exceedingly rare, and only a few cases have been reported. Saglam et al [ 4 ] described a 72- year- old woman with a single coronary artery anomaly who was admitted with atypical chest pain and may be a new subtype of the Lipton R-I subtype. Siddiqui et al [ 5 ] presented a single RCA arising from the right sinus of Valsalva in the absence of an equivalent left coronary artery system branches and associated mitral valve prolapse.…”
Section: Introductionmentioning
confidence: 99%